Oropharyngeal cancer as a driver of racial outcome disparities in squamous cell carcinoma of the head and neck: 10‐year experience at the University of Maryland Greenebaum Cancer Center. Issue 4 (30th June 2015) - Zandberg, Dan P.; Liu, Sandy; Goloubeva, Olga; Ord, Robert; Strome, Scott E.; Suntharalingam, Mohan; Taylor, Rodney; Morales, Robert E.; Wolf, Jeffrey S.; Zimrin, Ann; Lubek, Joshua E.; Schumaker, Lisa M.; et al.
Abstract: Background: Racial outcome disparities have been observed in head and neck squamous cell carcinoma (HNSCC) with diminished survival for black patients compared with white patients. Methods: We retrospectively analyzed 1318 patients with primary HNSCC treated at the University of Maryland Greenebaum Cancer Center (UMGCC) from 2000 to 2010. Results: Of all the patients, 65.9% were white, 30.7% were black, and 3.3% were of other races. Black patients were less likely to present with oral cavity cancer, and more likely to present with laryngeal or hypopharyngeal cancers. White patients were more likely to have early stage disease, especially in the oral cavity. Black race was independently associated with worse overall survival (OS) in the entire cohort. Black patients had a significantly worse OS among oral cavity and oropharyngeal cancers, with the largest disparity in oropharyngeal cancer. However, in multivariate analysis, race was only still significant in oropharyngeal cancer. Conclusion: We observed differences by race in distribution of disease site, stage, and OS. Survival disparity in the entire cohort was driven mostly by differences among oropharyngeal cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: 564–572, 2016